2021
DOI: 10.1021/acsami.1c02753
|View full text |Cite
|
Sign up to set email alerts
|

Highly Strong and Solvent-Resistant Cellulose Nanocrystal Photonic Films for Optical Coatings

Abstract: Cellulose nanocrystals (CNCs) are powerful photonic building blocks for the fabrication of biosourced colored films. A combination of the advantages of self-assembled CNCs and multiple templating agents offers access to the development of novel physicochemical sensors, structural coatings, and optic devices. However, due to the inherent brittleness and water instability of CNCderived materials, their further applications are widely questionable and restrictive. Here, a soft polymer of poly(vinyl alcohol) (PVA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 66 publications
(106 reference statements)
0
44
0
Order By: Relevance
“…[ 54 ] The n avg of these CNC/PEG–Eu composites hardly changed at 1.51. [ 53 ] According to the equation, the blueshift of the CPE–Red film was attributed to the decrease of P . The p‐ value corresponds to a distance between two continuous interlayers of the fracture surface of chiral nematic materials, which could be observed through the scanning electron microscope (SEM).…”
Section: Resultsmentioning
confidence: 99%
“…[ 54 ] The n avg of these CNC/PEG–Eu composites hardly changed at 1.51. [ 53 ] According to the equation, the blueshift of the CPE–Red film was attributed to the decrease of P . The p‐ value corresponds to a distance between two continuous interlayers of the fracture surface of chiral nematic materials, which could be observed through the scanning electron microscope (SEM).…”
Section: Resultsmentioning
confidence: 99%
“…There are additional reports on diverse cellulosic ChLC solid functional materials-such as structurally colored liquid marbles [80] and clay composites [81], photonic skins to visualize human motion [82,83], transistors for CPL-sensing [84], solvent-resistant photonic films [85], mechanically anisotropic composites [86], CPL-luminescent films incorporating quantum dots [87], pressure-sensitive aerogels [88], humidity-responsive photonic microarrays [89], and inkjet-printed photonic patterns [90]. These studies will facilitate expansion of the range of applications of cellulosic materials to industrial sectors in which cellulose is often considered to be incompatible with high performance.…”
Section: Other Cellulosic Chlc Solid Functional Materialsmentioning
confidence: 99%
“…[32][33][34] Chemical cross-linking methods can further improve the stiffness and solvent-resistance of these photonic composites. [35,36] Yet now, the above mechanical strain is only as high as ≈40%, which limits their applications in the field of high-performance devices or optics (Figure 1c). Recently, Kose et al reported a delicate and sophisticated strategy that packaged the chiral nematic structures of CNCs into hydrophobic Cellulose-based photonic structures.…”
Section: Introductionmentioning
confidence: 99%